2013
DOI: 10.1177/1533317513500837
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Safety

Abstract: This article explores how dyads of 186 community-dwelling individuals with a diagnosis of Alzheimer's disease or a related disorder (ADRD) and their caregivers (dyads) plan to respond to hurricane evacuation warnings in South Florida. Predictors of dyad evacuation for a category 1-3 storm include (1) a younger age of the person with an ADRD diagnosis, (2) the caregiver living in a different residence than the person with ADRD, (3) lack of hurricane shutters, and (4) lower income. A dyad is more likely to evacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Although still inconclusive, some cognitive impairments, such as mild cognitive impairment or dementia (Christensen et al 2013; Brown et al 2012) may reduce the ability to perceive and understand fire related cues and reduce the ability to perceive risk as well as to comply with evacuation procedures. So far, there are no studies that directly address RP and cognitive abilities in the context of evacuation and future studies are necessary to understand their role during evacuation.…”
Section: What Role Does Perceived Risk Play In Building Fire Evacuation?mentioning
confidence: 99%
“…Although still inconclusive, some cognitive impairments, such as mild cognitive impairment or dementia (Christensen et al 2013; Brown et al 2012) may reduce the ability to perceive and understand fire related cues and reduce the ability to perceive risk as well as to comply with evacuation procedures. So far, there are no studies that directly address RP and cognitive abilities in the context of evacuation and future studies are necessary to understand their role during evacuation.…”
Section: What Role Does Perceived Risk Play In Building Fire Evacuation?mentioning
confidence: 99%
“…People who live with small children and/or individuals with disabilities are more likely to indicate a higher level of preparedness. Other variables, such as education, income, and the perception of vulnerability, also tend to predict preparedness [6][7][8][9][10][11][12][13][14][15][16][17]. A number of other important psychological variables-such as key attitudes and beliefs-are likely to be useful in not only predicting but also marshalling people's willingness to prepare them for a disaster.…”
Section: Degree Of Preparedness According To Selected Variablesmentioning
confidence: 99%
“…34 Many older adults have chosen not to evacuate during hurricanes because they had survived previous incidents unscathed or evacuated unnecessarily in the past and so chose not to heed the present warnings. 36 Furthermore, disasters requiring evacuation or relocation can cause additional stress and mental health issues, with displaced older adults suffering greater psychological strain than those able to remain resident. 37 A 2013 US study found that, despite being at greater risk due to disruptions in infrastructure and support, older populations were inclined to shelter in place rather than evacuate.…”
Section: Psychological Effectsmentioning
confidence: 99%